Platelet Indices as Predictive Marker of Prognosis in Critically IllChildren Admitted to Pediatric Intensive Care Unit: An ObservationalStudy - Shrestha, Sailesh; K.C, Sri Ram; Gautam, Tilak; Khanal , Inesh; Shrestha, Sheshna; Pradhan , Bulbul (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Platelets play a key role in hemostasis and inflammatory processes. Routinely available platelet indices, platelet count, mean platelet volume, platelet distribution width, and plateletcrit may serve as useful prognostic markers in critically ill children. This study aimed to evaluate their role using routine complete blood count tests. Methods: A one-year prospective observational study was conducted in the Pediatric Intensive Care Unit of a tertiary hospital in Nepal from May 2023 to April 2024. Ethical approval was sought from the Institutional Review Committee (Ref: PMP2305161725). A convenience sampling technique was used. Platelet indices were compared with mortality, need for mechanical ventilation, inotropes, and hospital stay, using Receiver Operating Characteristic analysis to identify predictive cut-off values. Data were managed using Epidemiologic Information, Microsoft Excel, and Easy R. Results: Marked differences in platelet indices were noted across clinical outcomes. Survivors had significantly higher platelet count (270.75 ± 136.06) and plateletcrit (0.37 ± 0.15) than non-survivors (130.25 ± 86.72 and 0.21 ± 0.12, respectively; p < 0.001). Patients requiring inotropes had lower platelet count (184.32 ± 114.57) and plateletcrit (0.27 ± 0.16), but higher Mean platelet volume, platelet distribution width, and platelet distribution width-to-platelet count ratio (p < 0.001). Similarly, those requiring invasive mechanical ventilation had lower platelet count (195.01 ± 125.30) and plateletcrit (0.29 ± 0.16), but higher mean platelet volume and platelet distribution width-to-platelet count ratio (p < 0.001). Platelet count had the highest sensitivity (90.30%) for predicting mortality, while platelet distribution width had the highest specificity (86.7%). The platelet distribution width-to-platelet count ratio showed good sensitivity (77.40%) and specificity (79.20%) at a cutoff of 0.09. Conclusions: Platelet indices are valuable prognostic markers for critically ill children. However, further research with larger sample sizes, multicenter designs, and serial monitoring of platelet indices is needed to validate these findings.